2007
DOI: 10.1111/j.1365-3040.2007.01770.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomic and proteomic changes in the xylem sap of maize under drought

Abstract: Plants produce compounds in roots that are transported to shoots via the xylem sap. Some of these compounds are vital for signalling and adaptation to environmental stress such as drought. In this study, we screened the xylem sap using mass spectrometry to quantify the changes in new and previously identified sap constituents under extended drought. We detected and quantified the changes in the concentration of 31 compounds present in the xylem sap under progressively increasing drought stress. We found change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
195
3
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(215 citation statements)
references
References 71 publications
(90 reference statements)
13
195
3
4
Order By: Relevance
“…In summer, the drought-treated leaves also had higher concentrations of choline, which is involved in osmotic protection (40). These results are supported by some studies that found high concentrations of aromatic amino acids in plants under drought stress (41,42). These metabolomic differences were accompanied by an increase in K content, resulting in low C/K and N/K ratios and high K/P ratios that also were observed in summer (the drought season) (Figs.…”
Section: Discussionsupporting
confidence: 75%
“…In summer, the drought-treated leaves also had higher concentrations of choline, which is involved in osmotic protection (40). These results are supported by some studies that found high concentrations of aromatic amino acids in plants under drought stress (41,42). These metabolomic differences were accompanied by an increase in K content, resulting in low C/K and N/K ratios and high K/P ratios that also were observed in summer (the drought season) (Figs.…”
Section: Discussionsupporting
confidence: 75%
“…Ali and Ashraf (2011) studied the effect of drought treatment on the secondary metabolites of maize leaves and they found decreasing levels around 27 and 25% in total phenols for ʽEV-1098ʼ and ʽAgaiti-2002ʼ maize cultivars, being these results lower than the current data. Alvarez et al (2008) analysed xylem sap of ʽFR697ʼ maize cultivar after 12 days of drought treatment and they observed the same pattern of hydroxycinnamic acids composition of the present study, reporting that t-ferulic acid was the predominant with a decreasing of 46% of this compound after drought treatment and this result was higher than the current experiment, in addition p-coumaric acid increased 286% which is a different behaviour comparing with the current results. Vuletić et al (2014), analysed the effect of osmotic stress in root cell walls of the maize inbred line ʽVA35ʼ and they found that content of total phenols diminished 30%, which is in agree with this results, but they also found a different behaviour in the analysis of hydroxycinnamic acids since they observed an increase of 49 and 18% in t-ferulic acid and p-coumaric respectively.…”
Section: Total Phenols and Hydroxycinnamic Acidscontrasting
confidence: 56%
“…Our data in lignin content, are different to conclusions of other studies where proteomic and metabolonic analysis of lignin synthesis in maize were analysed; Vincent et al (2005), analysed the lignin content of the ʽF2ʼ ans ʽI0ʼ maize lines by thioacidolysis and they found that the lignin content was lower in leaves of plant subject to water deficit than in those of wellwatered plants and that was consistent with the levels of caffeic acid/5-hydroxyferulic 3-O-methyltransferase which is a key enzyme involved in lignin synthesis; in addition, Alvarez et al (2008) concluded that water stress reduces lignin biosynthesis of the maize root xylem vessels of the cultivar ʽFR697ʼ and they support this conclusion based in the analysis of metabolites which showed an increase of free monolignols in xylem sap. To best of our knowledge there are not data available on the effect of water stress on arabinoxylans content in maize, but there are some studies of the effect this abiotic stress on wheat arabinoxylans.…”
Section: Resultsmentioning
confidence: 92%
“…The authors theorize that an increase in hemicellulose may occur following short term or mild drought, but when drought conditions become more severe or prolonged the hemicellulose also decreases; however, further studies are needed to determine the mechanisms behind the observed trends. To the authors' knowledge, there is no literature regarding the effects of drought on lignin within mixed grasses, but the decrease could be attributed to alterations in phenylpropanoid compounds as reported previously for maize [44].…”
Section: Compositionmentioning
confidence: 88%
“…A proteomic study by Vincent et al found that lignin levels were lower in leaves of corn that were subjected to water stress [43]. Another study regarding the xylem sap of maize found that during drought there were increases in certain phenylpropanoids (monomeric units of lignin) and an increase in peroxidases, which could result in decreases of structural lignin [44]. Overall, drought conditions in 2012 within this field-scale study appear to have had an effect on all of the primary structural components within corn stover, which is in agreement with previous small-scale studies quantifying effects of water stress and heat stress on plant physiology [5].…”
Section: Compositionmentioning
confidence: 99%